Pulse shape simulations for organic scintillation detectors using Geant4 - Holroyd Caroline (EDP Sciences, 2021)
The accurate simulation of the temporal pulse shapes from organic scintillation detectors capable of pulse shape discrimination (PSD) presents the opportunity to assess the pulse shape discrimination of these detectors prior to fabrication. The aim of this study is the simulation of the temporal pulse shapes from EJ-276, a PSD-capable plastic scintillator developed by Eljen Technologies. PSD plastic scintillators are increasingly replacing organic liquid scintillators for the detection of neutrons in the presence of mixed radiation fields for nuclear security applications. Plastics are inexpensive, robust and can be fabricated in a variety of shapes and sizes. They offer a solid-state alternative to liquid scintillators which can be difficult to transport due to the risk of leakage. However, the PSD performance of plastic scintillators has been observed to decrease due to various factors which combine to influence the overall shape of the pulse. The Monte Carlo toolkit Geant4 has been used to simulate the temporal pulse shapes from an EJ-276 plastic scintillator coupled to a photomultiplier tube (PMT). All three decay time components of EJ-276 have been modelled, utilising new methods available in the latest version of Geant4, for two different scintillator geometries. The simulated n/γ pulse shapes reproduce the features important for PSD. Future work will involve integrating the temporal response of the PMT with existing pulse shape simulations. Simulated data will then be compared with experimental measurements.